OspA heterogeneity of Borrelia valaisiana confirmed by phenotypic and genotypic analyses - Bretz Anne-Gabrielle; Dayer Eric; Péter Olivier; Ryffel Karine; Godfroid Edmond (BMC Infectious Diseases, 2003)
Abstract Background Although European Borrelia burgdorferi sensu lato isolates have been divided into five genospecies, specific tools for the serotype characterization of only three genospecies are available. Monoclonals antibodies (mAbs) H3TS, D6 and I17.3 identify B. burgdorferi sensu stricto (ss.), B. garinii and B. afzelii respectively, but no mAbs are available to identify B. valaisiana. In the same way, specific primers exist to amplify the OspA gene of B. burgdorferi ss., B. garinii and B. afzelii. The aim of the study was to develop species-specific mAb and PCR primers for the phenotypic and genetic identification of B. valaisiana. Results This study describes a mAb that targets OspA of B. valaisiana and primers targeting the OspA gene of this species. As the monoclonal antibody A116k did not react with strains NE231, M7, M53 and Frank and no amplification was observed with strains NE231, M7 and M53, the existence of two subgroups among European B. valaisiana species was confirmed. Conclusions The association of both monoclonal antibody A116k and primers Bval 1F and Bval 1R allows to specific identification of the B. valaisiana isolates belonging to subgroup 1.